German Romanticism and Liturgical Theology Exploring the Potential of Organic Thinking - Geldhof, Joris 1976- (2016)
There is significant correspondence between two phenomena that are very rarely treated together yet reveal intriguing similarities: liturgical theology and German Romanticism. The key shared concept is "organism," a category expressing active life as well as coherence. It shows a way out of the deadlock caused by a simple opposition of objectivism and subjectivism. This article first of all presents an interesting kind of liturgical theology that was done by representatives of the Catholic Tübingen School, and then shows that the emerging Liturgical Movement was intrinsically Romantic in its theological approach to the liturgy.
Keywords: Catholic Tübingen School; German Romanticism; Lambert Beauduin; Liturgical Movement; Pius Parsch; Romano Guardini; Liturgical Theology; organism